Nepal’s Quest for Secured Boundaries and International Border Regime - Poudyal, Matrika (Journal of Foreign Affairs, 2023)
Nepal’s quest for secure and tranquil border assumes boundary diplomacy operating boundaries on the existing geostrategic settings conditioned by neighboring states India and China. It has yet to resolve several boundary problems with its neighboring states in its entirety though it has addressed many. So, it has to incorporate all the legal precisions and norms of border management system as practiced globally. This study revisits the essence of boundary diplomacy of Nepal in reference to international border regimes. The study primarily focuses on boundary delineation diplomacy along the Nepal-India and Nepal-China frontiers. It discusses Nepal’s border issues and boundary diplomacy with India and China with reference to the international border regime.